Studi Agama Model Islamologi Terapan Mohammed Arkoun - Kholili Hasib (Universitas Darussalam Gontor, 2014)
This article discusses the problems of renewal religious studies offered by the contemporary Islamic thinker of Algerian, Mohammed Arkoun. Arkoun study model is knownas‘Applied Islamology’, which is a method that comes from various different ideas to build a mutually reinforcing method. Basically, these models are influenced by an orientalist Richard Bestide, so what Arkoun produced wasactually a shynthesis. In his study, Arkoun adopted social-sciences approaches and Western humanities approaches, i.e. deconstruction. This study is a model of theological crticism on various Islamic studies which Arkoun considered itover based on Turath-centric and logos-centric andeven caused Islamic science to retrogress. In general, this model studied Islam based onthe paradigm ofhumanism approach. This approach delivers on two issues. First, because it involves a wide range of scientifical approaches, the study becomes overlapped with each other.Therefore, it is not easy to trace where this study will occur except the effect of deconstruction. Second, the concept of eclecticism used in his study isto releasethe Islamic tradition fromtheological and ideological- boundaries. He opened fullylogical explorationbeyond ideological prejudices, ethnicity, or religion. The method results in erroneous impressionof God, religion, divine revelation, prophets, and any otherreligious concepts. In essentials, Applied Islamology has a problem in the realm of theology and epistemology.